Low Birth Weight As the Predictors of Stunting in Children under Five Years in Teluknaga Sub District Province of Banten 2015 - Rahayu Diah Kusumawati, M; Marina, R; Endah Wuryaningsih, C (KnE Life Sciences, 2019)
Stunting in children under five years still becomes a health problem in Banten Province. This study aimed to analyze the determinants of stunting in children under five years in Teluknaga sub-district, Banten Province in 2015. Data were obtained from secondary data analysis using the primary survey data of Pos Keadilan Peduli Umat (PKPU) nutrition program in April 2015. The subsequent nutrient status assessment was performed using the calculation of longevity indicator by Age (PB/U) or Body Height by Age (TB/U) based on z-score according to WHO. Chi-square and multivariable logistic regression were used to analyze 290 children under five years old as the sample. The results showed that 70.7% of children were stunting. Bivariate analysis showed that birth weight of infants (p = 0.008), maternal employment status (p = 0.026), and average parents income (p = 0.012) have a significant relationship with the occurrence of stunting in infants. Birth weight of infants was the most dominant risk factor, among the variables. That is the children who were born with low birth weight was 3.12 times more likely to be stunted than those taken with normal weight after controlled by child sex, number of family members, education level of the father and mother, mother’s working status and average parents income (OR= 3.12, 95% CI: 1.38–7.03). Health programs to overcome stunting can be done through education about the importance of consuming proper nutrition and routine health checks in pregnant women and children under five. Also, training is also given to all women of childbearing age so that in the future can better understand the importance of maintaining nutritional status in adolescence, before pregnancy until pregnancy to give birth to healthy babies. Keywords: Low Birth Weight, Stunting, and Children.